Sustainability and Equity Challenges to Pension Systems: The Case of Lebanon - Mariusz Jarmuzek; Najla Nakhle (Journal of Banking and Financial Economics)
Reform of Lebanon’s pension system is indispensable. The country already faces fiscal sustainability risks, which will be compounded in the future by significantly higher pension- related spending and liabilities, mainly reflecting adverse demographics. In addition to sustainability issues, the pension system also suffers from equity shortcomings – Lebanon is the only MENA country that does not offer social security for retirees in the private sector. While several reform proposals have been formulated since the early 2000s, none has been implemented to date. Costs mount with every year of delay, so action is required soon to address these challenges.